APLIKASI SISTEM PENAGIHAN MENGGUNAKAN JALUR TERPENDEK PADA PERUSAHAAN LEASING PT. ILUFA - Tri Pujadi; Mariono Fabianus (Seminar Nasional Informatika (SEMNASIF), 2009)
Billing on PT. ILUFA a leasing company use coupon system as proof of daily installment. The problem began when the number of unpaid coupon increased so the finance found difficulties in calculating coupons nominal, while the administration was waiting the finance finished their job to note down billing coupons. With the increasing number of customers, difficulties to determine the shortest billing path arose. Methodology which is used to determine the billing shortest path algorithm is algorithm analysis, while the methodology for analysis and design of information system is object oriented, including create a new work flow for the administration and the finance with activity diagram. The result of algorithm analysis concludes that Dijkstra algorithm is more appropriate to determine shortest billing path. New work flow supports more effective and efficient business processes. Integrated information system is also facilitating coupon note down and coupon nominal calculation. After the billing information system implemented, the billing performance increase.